From village to city - The birth of the Islamic city in the Arabian Peninsula: Study in the Holy Quran - Kaddouri, Abdelkrim (Journal of Humanities & Social Sciences, 2020)
This article deals with a problematic subject The emergence of the city in the Arab Islamic civilization, and how to move from tribal fragmentation to living together, through monotheism, under the leadership of a prophet, judge and ruler. this by moving from the idea of a pagan tribal village governed by traditions which favor the privileged, to the city which rests on an agreed legal basis, this city represents the basis of Islamic civilization. The questions raised in this research are: how did the Arabs move to urbanization in the city of the Prophet? Was the foundation of this city a spontaneous historical fact or was it decreed in advance in the inspired book? By following the method of content analysis by describing the characteristics that distinguish a village from a city in the Noble Quran, we came to the conclusion that civilization in Islam was conceived in the founding text before being embodied by the call of the Prophet.
Keywords: The Holy Quran; paganism; monotheism; village; city; coexistence